Financial markets value reputation for Corporate Social Responsibility : a study of the South African mining sector - Munkuli, Bongani (My University, 2018)
Corporate social responsibility (CSR) is the obligation of business to participate in sustainable socio-economic development. However, there are uncertainties as to whether active participation in CSR practices lead to increased market valuation for South African mining firms. The purpose of the study is to evaluate the effect of corporate social responsibility practices on the market valuation of mining companies in South Africa. The study has five sub questions focussing on the variances in market valuation measures between mining corporations listed on the Johannesburg Securities Exchange’s Socially Responsible Investment Index (JSE SRI) and those that are not on the index over a period 2005-2015. A quantitative methodology was employed, utilising stata software to navigate through panel data that comprises observations on cross-section and time series. Both static and dynamic types of panel data approaches were employed as; ordinary least squares, fixed, and random effects models. The Arellano-Bond procedure were also used as a dynamic function to determine the long-run relationship between CSR and market value of a company. The sample include thirty eight corporations engaged in mining excluding those in exploration-only activities. Secondary data on market valuation measures was gathered from the Bureau of Financial Analysis database. As compared to the dominant qualitative research on CSR which shows a correlation between CSR and market valuation, the findings of this study which employed a quantitative approach indicate no significant relationship between CSR and market valuation in the mining sector, nor significant variances in market valuations between mining firms on the JSE SRI and those not on the index. Active participation in CSR activities does not lead to increased market valuation. The study has made the following contributions. It has provided an empirically based mining sector specific study on the effect of corporate social responsibility practices on the market valuation in South Africa; an area presently under-researched. Few studies have undertaken a quantitative approach which attempts to find a correlation between CSR and market valuation in the South African mining sector. The study has also provided an understanding that maximising shareholder wealth is still an important business goal despite the need to fulfil social demands. The study has further contributed to the literature by proposing an integrated framework for conceptualising CSR practices by mining firms in a developing economy.
A dissertation submitted to the Wits Business School, Faculty of Commerce, Law and Management, University of the Witwatersrand in fulfilment of the requirements for the Degree Doctor of Philosophy, Johannesburg March 2018
Keywords: Social responsibility of business--South Africa; Corporations--South Africa